COMPREHENSIVE REVIEW OF EMS QUALITY IMPROVEMENT PROGRAMS: EVALUATING METRICS, BENCHMARKING PRACTICES, AND CONTINUOUS IMPROVEMENT STRATEGIES - Abdulrahman Hamad Almurdif, TalalAbdulhadiG Almalki, Saud Mohammed Majrashi, Khalid MuaddiFadhelAlshehri, Fahad JaziIbnrubayq, Fahad Faleh Eid Alshammari, Muhannad Safar Almalki, Aziz Obaid Alanazi, (Chelonian Research Foundation, 2022)
This article demonstrates a detailed assessment of how the QI programs function in taking care of medical emergencies, which is called EMS. It rates a variety of indices; the best cases of practice, in addition to continuous progress evaluation, are among these. The study aims to present the current QI initiative design as used in the EMS system and offer recommendations to improve the outcomes of future initiatives. The review is done through an analysis of the current literature on the topic, relevant methodologies of improvement programs, visualization findings, and a discussion about the identified metrics, and it ends with a note of recommendations for future improvements. Keywords: Emergency Medical Services, Quality Improvement, Benchmarking, Continuous Improvement, Metrics, Evaluation